Hubungan Antara Pola Asuh Demokratis Orang Tua Dengan Empati Pada Remaja - ., Daisy Listiani (MOTIVASI, 2013)
Abstract.This study aims to determine whether there is a relationship between democratic parenting parents with empathy. Parenting is parenting is democratic, so that there is only one relationship that will be investigated in this study.The research was conducted at the junior high school students by the number of subjects 226 students from 3 different schools. Means of collecting data in the form of democratic questionnaire consisting of 24 items and empathy questionnaire consisting of 60 items, measuring instruments used in the form of Likert scale. Data were analyzed by multiple regression analysis using SPSS (Statistical packade for Social Science) 18 for Windows.From the analysis of the research data obtained by the correlation between democratic parenting with empathy for 0,100 to 0,000 p. This suggests that there is a highly significant correlation between democratic parenting with empathy.